"f(x, y, z)=-x^2+y^2+z^2-4xy-4xz" The matrix of the quadratic form is
"A=\\begin{pmatrix}\n -1 & -2 & -2 \\\\\n -2 & 1 & 0 \\\\ -2 & 0 &1\n\\end{pmatrix}" The characteristic equation is
"\\begin{vmatrix}\n -1-\\lambda & -2 & -2 \\\\\n -2 & 1-\\lambda & 0 \\\\ -2 & 0 & 1-\\lambda\n\\end{vmatrix}=0" Hence
"(1-\\lambda)({\\lambda}^2-9)=0""\\lambda_1=1, \\lambda_2=3, \\lambda_3=-3" Thus, the orthogonal canonical reduction is
"Q=\\begin{pmatrix}\n x' & y' & z' \\\\\n\\end{pmatrix}*\\begin{pmatrix}\n 1 & 0 & 0 \\\\\n 0 & 3 & 0 \\\\ 0 & 0 &-3\n\\end{pmatrix}*\\begin{pmatrix}\n x' \\\\\n y' \\\\ z'\n\\end{pmatrix}=(x')^2+3(y')^2-3(z')^2"Find eigenvectors:
"\\lambda_1=1""\\begin{pmatrix}\n -2 & -2 & -2 \\\\\n -2 & 0 & 0 \\\\ -2 & 0 &0\n\\end{pmatrix}*\\begin{pmatrix}\n v_1 \\\\\n v_2 \\\\ v_3\n\\end{pmatrix}=\\begin{pmatrix}\n 0 \\\\\n 0 \\\\ 0\n\\end{pmatrix}""\\begin{pmatrix}\n 1 & 0 & 0 \\\\\n 0 & 1 & 1 \\\\ 0 & 0 &0\n\\end{pmatrix}*\\begin{pmatrix}\n v_1 \\\\\n v_2 \\\\ v_3\n\\end{pmatrix}=\\begin{pmatrix}\n 0 \\\\\n 0 \\\\ 0\n\\end{pmatrix}""v=\\begin{pmatrix}\n 0 \\\\\n -1 \\\\ 1\n\\end{pmatrix}"The principal axis is
"{1 \\over \\sqrt{2}}\\begin{pmatrix}\n 0 \\\\\n -1 \\\\ 1\n\\end{pmatrix}""\\lambda_2=3""\\begin{pmatrix}\n -4 & -2 & -2 \\\\\n -2 & -2 & 0 \\\\ -2 & 0 &-2\n\\end{pmatrix}*\\begin{pmatrix}\n v_1 \\\\\n v_2 \\\\ v_3\n\\end{pmatrix}=\\begin{pmatrix}\n 0 \\\\\n 0 \\\\ 0\n\\end{pmatrix}""\\begin{pmatrix}\n 1 & 0 & 1 \\\\\n 0 & 1 & -1 \\\\ 0 & 0 & 0\n\\end{pmatrix}*\\begin{pmatrix}\n v_1 \\\\\n v_2 \\\\ v_3\n\\end{pmatrix}=\\begin{pmatrix}\n 0 \\\\\n 0 \\\\ 0\n\\end{pmatrix}""v=\\begin{pmatrix}\n -1 \\\\\n 1 \\\\ 1\n\\end{pmatrix}" The principal axis is
"{1 \\over \\sqrt{3}}\\begin{pmatrix}\n -1 \\\\\n 1 \\\\ 1\n\\end{pmatrix}""\\lambda_3=-3""\\begin{pmatrix}\n 2 & -2 & -2 \\\\\n -2 & 4 & 0 \\\\ -2 & 0 &4\n\\end{pmatrix}*\\begin{pmatrix}\n v_1 \\\\\n v_2 \\\\ v_3\n\\end{pmatrix}=\\begin{pmatrix}\n 0 \\\\\n 0 \\\\ 0\n\\end{pmatrix}""\\begin{pmatrix}\n 1 & 0 & -2 \\\\\n 0 & 1 & -1 \\\\ 0 & 0 & 0\n\\end{pmatrix}*\\begin{pmatrix}\n v_1 \\\\\n v_2 \\\\ v_3\n\\end{pmatrix}=\\begin{pmatrix}\n 0 \\\\\n 0 \\\\ 0\n\\end{pmatrix}""v=\\begin{pmatrix}\n 2 \\\\\n 1 \\\\ 1\n\\end{pmatrix}" The principal axis is
"{1 \\over \\sqrt{6}}\\begin{pmatrix}\n 2 \\\\\n 1 \\\\ 1\n\\end{pmatrix}"
Comments
Leave a comment